Mata Uang Dalam Pandangan Islam (Analisis Kritis Terhadap Bitcoin) - Alim, Sahirul; Fikriawan, Suad; Lubis, Ahmad Tarmizi (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Tis article examines the compatibility of Bitcoin with Sharia principles. Islam regulates financial transactions by prohibiting riba (interest), gharar (uncertainty), and maisir (speculation). This article explores whether Bitcoin, as a decentralized and volatile digital currency, can be considered halal in the Islamic context. The perspectives of various Islamic scholars are analyzed, considering technological, economic, and legal aspects. The article concludes that while Bitcoin possesses certain characteristics that align with Sharia, there remains legal and ethical uncertainty that requires further attention.